Skin Penetration and Permeation Properties of Transcutol®—Neat or Diluted Mixtures - Osborne, David W.; Musakhanian, Jasmine (AAPS PharmSciTech, 2018)
A heightened interest in (trans)dermal delivery is in part driven by the need to improve the existing skin therapies and also the demand for alternative routes of administration, notably for pharmaceutical actives with undesirable oral absorption characteristics. The premise of delivering difficult actives to the skin or via the skin however is weighed down by the barrier function properties of the stratum corneum. Short of disrupting the skin by physical means, scientists have resorted to formulation with excipients known to enhance the skin penetration and permeation of drugs. A vehicle that has emerged over the years as a safe solubilizer and enhancer for a broad range of drug actives is the highly purified NF/EP grade of diethylene glycol monoethyl ether (DEGEE) commercially known as Transcutol®. Whereas numerous studies affirm its enhancing effect on drug solubilization, percutaneous absorption rate, and/or drug retention in the skin, there are few publications that unite the body of the published literature in describing the precise role and mechanisms of action for Transcutol®. In view of the current mechanistic understanding of skin barrier properties, this paper takes on a retrospective review of the published works and critically evaluates the data for potential misses due to experimental variables such as formulation design, skin model, skin hydration levels, and drug properties. The goal of this review is to mitigate the incongruence of the published works and to construct a unified, comprehensive understanding of how Transcutol® influences skin penetration and permeation. Graphical Abstract Transcutol has affinity for the hydrophilic head groups of the stratum corneum structures